2011
DOI: 10.3109/11038128.2011.582651
|View full text |Cite
|
Sign up to set email alerts
|

Response actions to difficulties in using everyday technology after acquired brain injury

Abstract: Purpose: People with acquired brain injury (ABI) have difficulties using everyday technology (ET) in daily tasks at home and in the society. To support them managing the demands imposed by using ET, knowledge is needed about their response actions to the difficulties that occur during task performance, their conditions and efficiency. The aim of this study was to explore and describe what characterizes response actions to difficulties using ET, their conditions and how they influence the experiences of tasks i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 44 publications
2
3
0
Order By: Relevance
“…The management strategies that appeared among our participants concur with strategies that have been found in other studies in the context of everyday life in general among people with dementia (Clare, 2003; Harman & Clare, 2006; Nygård, 2004; Oyebode et al., 2009; Preston et al., 2007) or acquired brain injury (Larsson Lund, Lövgren Engström, & Lexell, 2012). Interestingly, our participants also used communication with and guidance from the technology as a management strategy, indicating that high-quality cues given by technology could serve as a built-in support for learning and using everyday technology for people with MCI or AD.…”
Section: Discussionsupporting
confidence: 88%
“…The management strategies that appeared among our participants concur with strategies that have been found in other studies in the context of everyday life in general among people with dementia (Clare, 2003; Harman & Clare, 2006; Nygård, 2004; Oyebode et al., 2009; Preston et al., 2007) or acquired brain injury (Larsson Lund, Lövgren Engström, & Lexell, 2012). Interestingly, our participants also used communication with and guidance from the technology as a management strategy, indicating that high-quality cues given by technology could serve as a built-in support for learning and using everyday technology for people with MCI or AD.…”
Section: Discussionsupporting
confidence: 88%
“…The participants had adopted management strategies to prevent or solve problems on their own both at work and in daily activities that were decisive for their possibility to continue working. This finding concurs with previous research [ 48 , 49 ] showing how people with cognitive impairment use a variety of self-initiated strategies to manage technology use and challenges in daily activities. The results indicate, similar to other research [ 49 ], a need to systematically assess each person’s management strategies in vocational rehabilitation.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the perceived difficulties of using ET ("use independently with difficulty" + "use with assistance of someone else"; Figure 3) were higher compared to the control group. Various difficulties of using ET have been identified and discussed in recent studies on elderly patients with dementia [11] [25] and people with ABI [15] [21]. Several types of ETs exist, and are es-sential for convenient modern day lives [10].…”
Section: Discussionmentioning
confidence: 99%
“…Fallahpour et al identified that the perceived difficulty in using ET is significantly increased among individuals with ABI with severe to moderate disability compared with controls [20], but this study did not include the situation of using ET. Occupational therapists are required to pay attention to the extent to which people with ABI have difficulty using ET due to their cognitive dysfunction [21].…”
Section: Introductionmentioning
confidence: 99%